2002
DOI: 10.1108/03068290210447003
|View full text |Cite
|
Sign up to set email alerts
|

Politics, society and financial sector reform in Bangladesh

Abstract: Examines the financial sector reform experience of Bangladesh. Finds that, while there have been some improvements in competition and efficiency, loan defaults still remain a significant problem. Also finds urban bias in loan allocation and shift of resources away from the rural sector. The main obstruction in the area of loan recovery is political interference. Provides a principal‐agent explanation of politicians’ behavior. Concludes that effective implementation of an optimal policy mix depends on complex p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 16 publications
0
30
0
Order By: Relevance
“…During the first democratic era (1972)(1973)(1974)(1975), Bangladesh followed a socialist economic model by nationalizing all its industries. The government established the ICAB, the Institute of Cost and Management Accountants of Bangladesh (ICMAB), the National Board of Revenue and the Bangladesh Bank (Chowdhury 2002). In the second democratic era (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), the major regulatory reforms of the early 1990s were aimed particularly at moving toward an open economy.…”
Section: Implementation Of Ifrs In Bangladeshmentioning
confidence: 99%
“…During the first democratic era (1972)(1973)(1974)(1975), Bangladesh followed a socialist economic model by nationalizing all its industries. The government established the ICAB, the Institute of Cost and Management Accountants of Bangladesh (ICMAB), the National Board of Revenue and the Bangladesh Bank (Chowdhury 2002). In the second democratic era (1991)(1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006), the major regulatory reforms of the early 1990s were aimed particularly at moving toward an open economy.…”
Section: Implementation Of Ifrs In Bangladeshmentioning
confidence: 99%
“…However, despite these measures and a reasonable growth rate of the economy, the private sector has not been able to contribute substantially to poverty alleviation. Rather, its role has been handicapped by crises in its own governance as well as in the state structure (Choudhury, 2002;CPD, 2002;Quadir, 2000;Sobhan, 2002).…”
Section: Some Critical Observations On the Role Of The Private Sectormentioning
confidence: 97%
“…Lower echelons of the judiciary have been seriously corrupted (Hannan, 2004;Shelley, 2004;Sobhan, 2004). Violence-much of it perpetrated by and more of it condoned and even encouraged by the state itself-and corruption have become the rule, increasingly so in recent years (Blair, 2004;Choudhury, 2002;Islam, 2004Sobhan, 2004. In the countryside, gangsters have come to operate virtually parallel justice systems, murdering opponents in the name of vandalism, often under the protection of the police (Blair, 2004).…”
Section: Crisis In State Structure and Its Fall-out On Poverty Allevimentioning
confidence: 98%
“…Chowdhury (2002) observed that the banking industry of Bangladesh is a mixed one comprising nationalized, private and foreign commercial banks. Many efforts have been made to explain the performance of these banks.…”
Section: Introductionmentioning
confidence: 99%